2022
DOI: 10.1111/ceo.14168
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for the development or progression of diabetic retinopathy in pregnancy: Meta‐analysis and systematic review

Abstract: Background Diabetic retinopathy (DR) is the leading cause of blindness in the working‐age population, and it increases in severity during pregnancy. Methods Systematic review of literature from PubMed, Cochrane Library and Web of Science using keywords ‘diabetic retinopathy’ and ‘pregnancy’ and ‘progression’ from inception to 2021 was completed. Included studies were (1) peer‐reviewed observational studies addressing progression/development of DR in pregnancy, (2) provided the number of diabetic patients that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…Regrettably, data pertaining to several known risk factors for retinopathy progression, such as blood pressure, pre-eclampsia, and blood sugar control, are not routinely collected as part of eye screening in the UK and therefore were not included in our data analysis [ 15 ]. While hypertension is known to be a powerful risk factor for retinopathy progression [ 15 ], both a recent retrospective [ 11 ] and a prospective study of pregnant women with insulin-dependent diabetes [ 10 ] failed to correlate arterial hypertension with any increased risk of progression in women with tightly controlled blood sugar levels. Similarly, in Pappot et al’s retrospective cohort analysis of 348 women with diabetes, no women without retinopathy and HbA1c < 53 mmol/mol (7.0%) in early pregnancy developed sight-threatening retinopathy and 94% (165/175) did not develop any retinopathy [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regrettably, data pertaining to several known risk factors for retinopathy progression, such as blood pressure, pre-eclampsia, and blood sugar control, are not routinely collected as part of eye screening in the UK and therefore were not included in our data analysis [ 15 ]. While hypertension is known to be a powerful risk factor for retinopathy progression [ 15 ], both a recent retrospective [ 11 ] and a prospective study of pregnant women with insulin-dependent diabetes [ 10 ] failed to correlate arterial hypertension with any increased risk of progression in women with tightly controlled blood sugar levels. Similarly, in Pappot et al’s retrospective cohort analysis of 348 women with diabetes, no women without retinopathy and HbA1c < 53 mmol/mol (7.0%) in early pregnancy developed sight-threatening retinopathy and 94% (165/175) did not develop any retinopathy [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy itself is a proven risk factor for complications for both mother and infant [12][13][14] and has been detailed in previous studies [15] affecting almost every organ system [16][17][18]. However, development and progression of severe ocular complications such as DR and macular edema have fewer studies, though recent literature has provided more detail on modifiable and non-modifiable risk factors [8]. These complications can lead to blindness [19] and severe changes in VA.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue, Sarvepalli and colleagues analysed the findings of studies in this field from the past 40 years to determine the progression rate of DR and the risk factors that may be related to DR progression during pregnancy. 1 They found that 17.65% of pregnant women with pre-existing diabetes developed new DR, 21.49% of women with nonproliferative DR (NPDR) at early pregnancy progressed, and among those with proliferative DR (PDR) at early pregnancy, 38.32% experienced worsening. Thus, the presence and severity of DR in early pregnancy are clear predictors of DR progression-the worse it is early on, the worse it is likely to become.…”
mentioning
confidence: 99%
“…As a result, current guidelines are somewhat vague and do not give any indication of which patients may be at greatest risk of progression during pregnancy. In this issue, Sarvepalli and colleagues analysed the findings of studies in this field from the past 40 years to determine the progression rate of DR and the risk factors that may be related to DR progression during pregnancy 1 . They found that 17.65% of pregnant women with pre‐existing diabetes developed new DR, 21.49% of women with non‐proliferative DR (NPDR) at early pregnancy progressed, and among those with proliferative DR (PDR) at early pregnancy, 38.32% experienced worsening.…”
mentioning
confidence: 99%